DATA MINING KLASIFIKASI KEPRIBADIAN SISWA SMP NEGERI 5 JEPARA MENGGUNAKAN METODE DECISION TREE ALGORITMA C4.5 - Adjie Kukuh Wahyudi; Noor Azizah; Heru Saputro (Universitas Islam Nahdlatul Ulama Jepara, 2022)
In the world of education, there are many supporting factors to achieve success in the learning process, from teachers, materials, to students. The thing that still a problem for many educators is how to provide material or learning with various personality characteristics of students who arrive is still a difficulty for educators, this is what encourages the author to carry out this research, so that it can help educators to know the personality of each student. So research Data Mining Personality Classification of SMP Negeri 5 Jepara Students Using Decision Tree Algorithm C4.5 method. By using the decision method tree algorithm C4.5, this data mining can produce perfect output in classifying students' personalities, in this case study at SMP N 5 Jepara.These results are indicated by filling out questionnaires by researchers to 100 students and 1 teacher BP SMP Negeri 5 Jepara.